Paysage et intensification de l’élevage en Amazonie brésilienne : De nouvelles dynamiques spatio-temporelles à l’échelle des exploitations agricoles - Sophie Sylvie Plassin; René Poccard-Chapuis; François Laurent; Marie-Gabrielle Piketty; Gustavo Pimentel Martinez; Jean-François Tourrand (Confins)
In the Brazilian Amazon, extensive cattle ranching expansion has been the main driver of deforestation since the last four decades and led to large extent of degraded lands. Great expectations have been placed in land use intensification through the restoration of degraded pastures, improving livestock performance and conserving forest. Despite such environmental challenges, the process of intensification at farm scale is poorly understood, especially in spatial terms. In this study, we produce knowledge about cattle ranchers’ decisions regarding land-use intensification, within a landscape approach and farm trajectories framework. The landscape, conceptualized as a spatially agroecosystem, enables to analyze the interactions between cattle ranchers’ decisions and spatially distributed natural resources, while the study of trajectories (sequence of farm’s phases) aims at understanding farm’s long-term socio-technical changes and the links with landscape dynamic. We used semi-structured and retrospective interviews as well as complex graphic model to analyze diachronically spatial logics of land-use intensification in six cattle farms, in old frontiers. Our results show that cattle ranchers, in their large diversity, have different strategies regarding land-use intensification, aimed at optimizing the use of natural resources spatially. Pastureland intensification is not spatially uniform, leading to less uniform landscape patterns than during agricultural expansion. This dynamic is more complex and efficient than restoring degraded pasture. We recommend the implementation of policies that promote the transition towards eco-efficient practices and to plan the spatial organization of intensified pasture and secondary forest regeneration to enable better use of natural resources in livestock systems in the Brazilian Amazon.